The Father Who Redeems and the Son Who Obeys : Consideration of Paul's Teaching in Romans. - Khobnya, Svetlana (James Clarke & Co, 2014)
The idea of God the Father has attracted scholarly attention for centuries, especially in terms of the revelation of God's fatherhood through the Son. ''The Father Who Redeems and the Son Who Obeys'' balances the Christological perspective on God's nature with the image of God the Father that has its roots in the Old Testament, and is more prominent in the Second Temple period than sometimes acknowledged. For Paul, God is the Father who redeems. The Old Testament imagery that shaped the Israelites' conception of God's interaction with them (and which was a basis for God's future restoration of.